How language background impacts learners studying International Financial Reporting Standards: a cognitive load theory perspective. (3rd September 2021) - King, Rosemary; Blayney, Paul; Sweller, John
ABSTRACT: This study offers evidence of the impact of language background on the performance of students enrolled in an accounting study unit. It aims to quantify the effects of language background on performance in essay questions, compared to calculation questions requiring an application of procedures. Marks were collected from 2850 students. The results were examined using a two-way mixed ANOVA. A significant interaction was found. There was no significant difference in performance on calculation questions between those students with an English language background and students with a language background other than English. Students with an English language background performed better on essay questions. Cognitive load theory suggests that these differences in results are due to the burden of additional cognitive translation processes taking up restricted working memory resources for students with a language background other than English on questions with a heavy language component. Implications for accounting educators are discussed.